PENGARUH KEPUASAN KERJA TERHADAP NIAT KELUAR DENGAN KOMITMEN ORGANISASIONAL AUDITOR SEBAGAI INTERVENING - Titik Rianawati; Sunarto Sunarto (STIE Pelita Nusantara Semarang, 2018)
The research aims to determine the effect of job satisfaction to wards the resigned intention with organizational komitment mediation and auditor job, the reseach is an empirical study to publikc account office in Semarang. The analysis methode used in this research in the classiccal Assumption test,covering normality test,autocorelation test, multicoloniaritas test, and regression fit model test used simultaneous test F, coefficient determination test, hypotesis test, and mediation test. The results of the research show that job satisfaction have positif significance effect to wards organizational commitment. Shown by the value of t count 17,546 > t table 1,992 by the significant 0,000 < 0,05. Job satisfaction have negative significance effect to resigned intention. Shown by the value of t count -2,449 > t table 1,992 by the significant 0,017 < 0,05. Organizational comitment has negatif significant effect. It is shown by the value of count -2,183 < t table 1,992 with the significancy 0,033 < 0,05. The result of this test also shows that organization commitment mediates the job satisfaction to wards resigned intention. It is shown by t count 2,29 > t table 1,992.